Combination of Sildenafil and Ba2+ at a Low Concentration Show a Significant Synergistic Inhibition of Inward Rectifier Potassium Current Resulting in Action Potential Prolongation - Macháček, Martin; Švecová, Olga; Bébarová, Markéta (Frontiers in Pharmacology, 2022)
Sildenafil (Viagra) is a vasodilator mainly used in the treatment of erectile dysfunction. Atrial or ventricular fibrillation may rarely occur as a side effect during sildenafil therapy. Although changes in inward rectifier potassium currents including IK1 are known to contribute to the pathogenesis of fibrillation, the effect of sildenafil on IK1 has not been studied. In experiments, Ba2+ is used as a specific inhibitor of IK1 at high concentrations (usually 100 µM). Being an environmental contaminant, it is also present in the human body; Ba2+ plasmatic concentrations up to 1.5 µM are usually reported in the general population. This study was primarily aimed to investigate changes of IK1 induced by sildenafil in a wide range of concentrations (0.1-100 µM). Additionally, the effect of the combination of sildenafil and Ba2+ at selected clinically-relevant concentrations was tested, at 0.1 µM both on IK1 and on the action potential duration (APD). Experiments were performed by the whole-cell patch-clamp technique on enzymatically isolated rat ventricular cardiomyocytes, mostly at 23°C with the exception of APD measurements which were performed at 37°C as well. Sildenafil caused a significant, reversible, and concentration-dependent inhibition of IK1 that did not differ at -50 and -110 mV. Simultaneous application of sildenafil and Ba2+ at 0.1 µM revealed a massive inhibition of both inward and outward components of IK1 (this synergy was missing at other tested combinations). The combined effect at 0.1 µM (45.7 ± 5.7 and 43.0 ± 6.9 % inhibition at -50 and -110 mV, respectively) was significantly higher than a simple sum of almost negligible effects of the individual substances and it led to a significant prolongation of APD at both 23 and 37°C. To our knowledge, similar potentiation of the drug-channel interaction has not been described. The observed massive inhibition of IK1 induced by a combined action of the vasodilator sildenafil and environmental contaminant Ba2+ at a low concentration and resulting in a significant APD prolongation may contribute to the genesis of arrhythmias observed in some patients treated with sildenafil.